Comparison between cell culture and serology for detecting Chlamydia trachomatis in women seeking abortion. Issue 1 (January 1988) - Csángó, P A; Sarov, B; Schiøtz, H; Sarov, I
Abstract : The efficiency of an immunoperoxidase serological assay and culture of Chlamydia trachomatis were compared in 127 women seeking first trimester abortion. Serum IgG and IgA antibodies specific for C trachomatis were detected by a single serovar (L2) inclusion immunoperoxidase assay (IPA). Eighty (63%) women were seropositive for chlamydial IgG and 31 (24%) for IgA antibodies. C trachomatis was isolated from 21 of 127 (17%) women. Twenty of the 80 women (25%) seropositive for specific IgG antibodies and one of 47 (2%) patients without these antibodies were culture positive (p less than 0.001). Compared with isolation, chlamydial antibodies at a titre of greater than or equal to 16 showed high sensitivity and negative predictive value (95% and 98%, respectively), but low specificity and efficiency (43% and 52%, respectively). Chlamydial IgA antibodies at a titre of greater than or equal to 8 showed low sensitivity (52%), but a higher specificity, negative predictive value, and efficiency of 81%, 90%, and 76%, respectively. C trachomatis IgG antibodies at a titre of 16 as determined by IPA can be used as an efficient negative exclusion marker for active chlamydial infection in screening women seeking abortion.